2022
DOI: 10.1186/s40645-021-00461-4
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the geological structure and mechanical properties due to the collision of multiple basement topographic highs in a forearc accretionary wedge: insights from numerical simulations

Abstract: We propose a conceptual geological model for the collision of multiple basement topographic highs (BTHs; e.g., seamounts, ridges, and horsts) with a forearc accretionary wedge. Even though there are many BTHs on an oceanic plate, there are few examples of modeling the collision of multiple BTHs. We conducted numerical simulations using the discrete element method to examine the effects of three BTH collisions with forearcs. The typical geological structure associated with a BTH collision was reproduced during … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…The discontinuous basal décollement in the type 3 and 4 models produced similar geometric and kinematic features as those caused by seamount/ridge subduction, although our sand mound was neither rigid nor fixed to the base (cf., Dominguez et al., 2000; Lallemand et al., 1992; Miyakawa et al., 2022; Noda et al., 2020; Okuma et al., 2022; Ruh et al., 2016). For the type 3 model, when the sand mound starts to be subducted at the deformation front, the wedge enters a compressively unstable regime in order to adjust to the higher basal friction until the wedge reaches a new equilibrium with a higher taper angle (Figure 14a).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The discontinuous basal décollement in the type 3 and 4 models produced similar geometric and kinematic features as those caused by seamount/ridge subduction, although our sand mound was neither rigid nor fixed to the base (cf., Dominguez et al., 2000; Lallemand et al., 1992; Miyakawa et al., 2022; Noda et al., 2020; Okuma et al., 2022; Ruh et al., 2016). For the type 3 model, when the sand mound starts to be subducted at the deformation front, the wedge enters a compressively unstable regime in order to adjust to the higher basal friction until the wedge reaches a new equilibrium with a higher taper angle (Figure 14a).…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al, 2020). When a high-friction patch on the plate interface works as a barrier to stress transmission on the basal décollement, the wedge deformation includes indentation or slope failure on the surface topography, widening of the brittle-damaged zone on the plate interface, and promotion of the underthrusting of subducted sediments beneath the wedge (Dominguez et al, 2000;Miyakawa et al, 2022;Morgan & Bangs, 2017;Noda et al, 2020;Okuma et al, 2022;Wang & Bilek, 2011). In summary, these previous studies have shown that accretion is a cyclical process, including frontal accretion and underthrusting, and that the décollement configurations affect the wedge architecture.…”
Section: Previous Modeling Studies Of Accretionary Wedgesmentioning
confidence: 99%
See 2 more Smart Citations
“…Miyakawa et al. (2022) construct a numerical model as a function of temperature and investigate a model in which splay faults develop and dislocate on geological timescales. Conin et al.…”
Section: Introductionmentioning
confidence: 99%